Great Recession in California and Nevada : Comparing Employment Effects in Two Neighboring Western States - Falls, Sam; Fisher, Sara; Markert, James; Navara, Tony (My University, 2013)
The economic downturn that began at the end of 2008 has become known as the Great Recession and by most accounts the economy has been slow to recover from this hit. The standard way of judging the severity of a recession and success of a recovery is to look at labor market information. The purpose of this study was to compare the impact of the Great Recession and the subsequent recovery in the two neighboring Western states of California and Nevada to the United States as a whole.
Color poster with text, tables, and graphs.
Keywords: Global Financial Crisis, 2008-2009; Great Recession; Unemployment--California; Unemployment--Nevada; Unemployment--United States; Posters